Clinical Value of Serum Amyloid-A Protein, High-density Lipoprotein Cholesterol and Apolipoprotein-A1 in the Diagnosis and Follow-up of Neonatal Sepsis. Issue 8 (August 2020) - Bourika, Vasiliki; Hantzi, Eugenia; Michos, Athanasios; Margeli, Alexandra; Papassotiriou, Ioannis; Siahanidou, Tania
Abstract : Background: To evaluate the performance of serum amyloid-A (SAA), high-density lipoprotein cholesterol (HDL-C) and apolipoprotein-A1 (Apo-A1) levels in the identification and monitoring of neonatal sepsis. Methods: This prospective study included 113 full-term septic neonates (postnatal age 4–28 days) admitted to the Special Care Neonatal Unit of a University Hospital from January 1, 2016, to April 30, 2019, and 68 healthy neonates (controls). Blood samples were drawn serially in septic neonates at enrollment and on days 1, 3 and 7, and once in controls, for SAA, HDL-C and Apo-A1 determination. Results: At enrollment, SAA levels were significantly higher in septic neonates in comparison with controls (median 50.7 vs. 3.5 mg/L; P < 0.0001); HDL-C and Apo-A1 levels were significantly lower in patients than in controls ( P < 0.001 and P < 0.006, respectively). SAA levels were higher in culture-positive compared with culture-negative sepsis (median 202.0 vs. 14.2 mg/L; P < 0.0001). HDL-C and Apo-A1 levels did not differ significantly between culture-positive and culture-negative sepsis. Receiver operating characteristic curve analysis of SAA levels at enrollment resulted in significant areas under the curve (AUC) for detecting sepsis {AUC = 0.929 [95% confidence interval: 0.885–0.973]; P < 0.0001} and also for discriminating between culture-positive and culture-negative sepsis [AUC = 0.933 (95% confidence interval: 0.882–0.984); P < 0.0001]. The combination of HDL-C and Apo-A1 with SAA increased its diagnostic performance. Furthermore, serial SAA levels following enrollment could indicate clinical response in septic neonates. Conclusions: SAA seems to be a useful biomarker for identification and monitoring of neonatal sepsis, and also for discriminating between culture-positive and culture-negative sepsis. HDL-C and Apo-A1 could be used as complementary markers. Abstract : Supplemental Digital Content is available in the text.